2009
DOI: 10.48550/arxiv.0906.5454
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

FCNC Processes in the Littlest Higgs Model with T-Parity: an Update

Abstract: We update our 2006-2007 results for FCNC processes in the Littlest Higgs model with T-parity (LHT). The removal of the logarithmic UV cutoff dependence in our previous results through a new contribution to the Z 0 -penguin diagrams identified by Goto et al. and del Aguila et al., while making the deviations from the SM expectations in the quark sector less spectacular, still allows for sizable new physics effects in K → πν ν and K L → π 0 + − decays and in the CP-asymmetry S ψφ with the latter unaffected by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
124
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 54 publications
(129 citation statements)
references
References 75 publications
4
124
1
Order By: Relevance
“…This complements our previous calculations of µ → eγ and µ → eee in [24] and those in [23,25]. The results for the Ti nucleus are in good agreement with previous work [23,26] where a degenerate mirror quark sector was assumed. Here we have also considered the effect of a more general quark sector where we include non-degenerate mirror quark masses and arbitrary mixings.…”
Section: Introductionsupporting
confidence: 92%
See 3 more Smart Citations
“…This complements our previous calculations of µ → eγ and µ → eee in [24] and those in [23,25]. The results for the Ti nucleus are in good agreement with previous work [23,26] where a degenerate mirror quark sector was assumed. Here we have also considered the effect of a more general quark sector where we include non-degenerate mirror quark masses and arbitrary mixings.…”
Section: Introductionsupporting
confidence: 92%
“…Here we have also considered the effect of a more general quark sector where we include non-degenerate mirror quark masses and arbitrary mixings. We have also found that µ N → e N is one-loop finite [24,26,27]. This is apparent for box diagrams but not for Z penguins.…”
Section: Introductionmentioning
confidence: 64%
See 2 more Smart Citations
“…Constraints within various supersymmetric extensions are analyzed in [20][21][22][23][24][25][26][27][28][29][30][31] (for overviews see [3,35]). Bounds on the Little Higgs Model with T-parity have also been presented [36]. Finally, model-independent analyses in the effective field theory approach without [37] and with the assumption of minimal flavor violation [10,11] also show the strong constraining power of the B → X s γ branching fraction.…”
Section: Introductionmentioning
confidence: 95%